The Role of Defense Diplomacy for The Development of The Indonesian Defense Industry - Fajar Agus Riyadi; Istin Marlena Dewi (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2022)
Indonesia's defense policy in the form of a Minimum Essential Force (MEF) can produce apolicy on developing Indonesia's defense posture until 2024. Efforts to meet the needs of Defense and Security Equipment Tools (Alpalhankam) implemented to date are still trying to fulfill MEF needs until now one hundred percent. The fulfillment of the needs Defense and Security Agency continues to pursue through procurement from the foreign and local defense industries. The establishment of the KKIP in 2010 and the issuance of Law Number 12 of 2012 have legitimized the government's support in efforts to develop the national defense industry. With the government's policy related to the defense industry, it will encourage the ability of the local defense industry to realize independence which carries out by defense diplomacy. The problem to be investigated is the government's role in defense diplomacy to support the development of the Indonesian defense industry. The research uses a qualitative descriptive method with data collection techniques through snowball sampling and literature study. The study results show that defense diplomacy carried out by the current government, especially the Minister of Defense Prabowo Subianto, can encourage defense cooperation that can support the development of the Indonesian defense industry while still prioritizing the principle of being accessible active, and non-alliance. Furthermore, the defense diplomacy strategy needs to be developed more broadly by offering a broader and more profitable defense industry cooperation scheme.